2023
DOI: 10.21037/jgo-23-217
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of ENC1 in gastrointestinal tumors: Bioinformatics analysis based on a public gene database

Abstract: Background To investigate the expression characteristics of ectodermal-neural cortex 1 ( ENC1 ) in gastrointestinal tumors and its potential value in judging the prognosis of patient survival. Methods RNA sequence (RNA-seq) data and patient survival data related to stomach adenocarcinoma (STAD) and colon adenocarcinoma (COAD) in gastric cancer and colon cancer from The Cancer Genome Atlas (TCGA) were downloaded for expression difference analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In addition to the upregulated transcripts, our study also sheds light on the significant downregulation of specific genes reported in various cancer forms. ENC1, SLAMF7 GREB1, EPHA7, CDH6, PKHD1, FBG, FLT3, ADAR2, and ANKRD1 are prominent in this category, suggesting their potential as therapeutic targets in various cancers [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62].…”
Section: Promising Effects Of Downregulated Transcripts On Tumor Grow...mentioning
confidence: 99%
“…In addition to the upregulated transcripts, our study also sheds light on the significant downregulation of specific genes reported in various cancer forms. ENC1, SLAMF7 GREB1, EPHA7, CDH6, PKHD1, FBG, FLT3, ADAR2, and ANKRD1 are prominent in this category, suggesting their potential as therapeutic targets in various cancers [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62].…”
Section: Promising Effects Of Downregulated Transcripts On Tumor Grow...mentioning
confidence: 99%